2010
DOI: 10.1111/j.1532-849x.2010.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Coronal Microleakage in Access Cavities through Metal Ceramic Crowns Restored with Resin Composites

Abstract: All tested techniques and materials in this study showed microleakage. Packable composite while a flowable liner showed a marginally better result than packable composite alone. Excessive thermocycling resulted in significant differences among the test groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Other aging methods include water storage and thermomechanical loading. Previous studies showed statistically significant difference between thermocycling and water storage, thermocycling being superior [ 40 ]. Furthermore, thermomechanical loading is superior to thermocycling, with a statistically significant difference [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other aging methods include water storage and thermomechanical loading. Previous studies showed statistically significant difference between thermocycling and water storage, thermocycling being superior [ 40 ]. Furthermore, thermomechanical loading is superior to thermocycling, with a statistically significant difference [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repair of the access cavity is of clinical importance with regard to restoring coronal seal. 5 Since SEM images of this study are insufficient to interpret coronal seal efficiency of the repaired crowns, future studies are needed to establish the most appropriate crown and repair material for restoring coronal seal after endodontic treatment.…”
Section: / Discussionmentioning
confidence: 95%
“…3 Second, the seal of the repaired access cavity is crucial to prevent microleakage, thus ensuring the long-term success of the restoration and endodontic treatment. 4,5 Last but not least, the fracture strength of the accessed crown may be compromised. 3,6 The previous studies evaluating the influence of simulated endodontic access preparation on all-ceramic crowns have reported several factors affecting the fracture strength such as the choice of luting cement, 6 the grit size of the rotary instrument used for the access preparation, 6 the repair filling method of the access cavity, 7 and as the most frequently investigated parameter, the type of all-ceramic material used.…”
Section: / Introductionmentioning
confidence: 99%
“…En contraparte, en este estudio se observaron proporciones de filtración en todas las piezas y, aunque no sean significativas, algunas como el Permaseal presentaron filtración a niveles de 90%. Dicha filtración es contemplada en los estudios propuestos, (Fakhri, 2009;Al-Maqtari 2010), quienes mencionaron que los conductos radiculares sellados pueden ser recontaminados bajo varias circunstancias, y algunas de ellas pudieron tener influencia en los resultados del presente estudio.…”
Section: Resultsunclassified